Evaluation of the Quality of Four Root Canal Obturation Techniques Using Micro-Computed Tomography - Naseri, Mandana; Kangarlou, Ali; Khavid, Atefeh; Goodini, Mostafa (Iranian Endodontic Journal, 2013)
Introduction: One of the key factors in successful endodontic therapy is to adequately fill the root canals. The aim of this in vitro study was to compare the quality of four different root canal obturation techniques: cold lateral condensation (CLC), warm vertical condensation (WVC), Obtura II (OII) and Gutta Flow (GF) by using micro-computed tomography (micro CT). Materials and Methods: A total of 20 extracted maxillary first molars prepared with ProTaper files, were randomly divided into four groups. Micro CT was used to measure the internal volume of root canals. Following application of AH26 sealer to canal obturation, new micro-CT images were taken and the volume percentage (VP) of voids, gutta-percha and sealer at different levels were calculated with CT software. Data was statistically analyzed using Kruskal-Wallis and Mann-Whitney U tests. Results: The highest percentage of filling material was observed in GF group followed by OII with no statistically significant difference (P>0.05). These two groups had a significantly more acceptable filling than WVC and CLC groups (P<0.05). Voids were detected in all samples. There was a significant difference between the highest and the lowest percentage of voids in CLC (19.6%) and GF groups (6.7%), respectively. In the apical third, CLC and OII showed the highest and the lowest percentage of voids (5.5% and 2.6%) and the lowest and highest percentage of gutta-percha (76.52% and 94.26%), respectively. These differences were statistically significant (P<0.05). Conclusion: None of the root canal filled teeth were gap-free. GF and CLC techniques showed the highest and lowest VP of obturation materials, respectively.